Feeding behaviour of domestic ruminants in sahelian zone - Dicko, M.S.; Sangare, M. (Australian Academy of Science, 1986)
Report of a study conducted to determine the relationship between environment, herd management and grazing behaviour of domestic ruminants in the Sahelian zone